COMPARATIVE ANALYSIS OF INNOVATION OF BANKING BUSINESS IN UKRAINE AND FOREIGN COUNTRIES - SHKILNIAK, Kostyantyn (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Innovation has become a key success factor in today’s banking business, contributing to increased efficiency, security and convenience of financial services. In the conditions of rapid development of technologies and globalization of financial markets, banking institutions are forced to constantly adapt to new challenges and opportunities. A comparative analysis of the innovative development of banking business in Ukraine and foreign countries will reveal the strengths and weaknesses of various approaches to the implementation of innovations, evaluate the effectiveness of state policies, institutional structures and corporate strategies. Comparison with foreign countries provides an opportunity to take into account best practices and avoid mistakes, which allows to implement innovations more effectively and contribute to the sustainable development of the financial system. Carrying out a comparative analysis of banking business innovation in Ukraine and foreign countries. In the research process, both general scientific and special methods of cognition were used, namely: system analysis, methods of systematization and generalization, logical, monographic, comparative and tabular methods. The classification of banking innovations on the international market is presented and it is determined that successful banks choose innovative development as a tool for achieving competitive advantage, taking into account all benefits and threats. The results of a comparative analysis of the innovation of banking business in Ukraine and foreign countries are given and it is found that the main trends of innovation and development of banks include a strong relationship between banks and clients, integration of banks and IT departments, interaction between banks and social networks, as well as implementation of modern technologies. Innovative products used in the practical activities of Ukrainian banks are singled out, and it is established that banks more often use artificial intelligence tools that enable the use of more innovative technologies, as a result of which companies have the opportunity to reduce costs and improve the quality of the services they provide. Further research should be aimed at developing measures to accelerate the adoption of innovation, such as digital wallets and biometric identification, which will help improve the quality of customer service and increase the efficiency of banking operations.